2014
DOI: 10.17813/maiq.19.1.e541814nt57q31t0
|View full text |Cite
|
Sign up to set email alerts
|

Allies Forging Collective Identity: Embodiment and Emotions on the Migrant Trail

Abstract: This article examines how embodied experience and the accompanying emotions help social movement allies to forge collective identity. The analysis is based on the Migrant Trail, an annual protest event in which allies of the border-justice movement spend a week walking seventy-five miles through the U.S.-Mexico borderlands to protest migrant deaths. Original data include four years of participant observation, interviews conducted during the 2011 Migrant Trail, and surveys conducted a year and a half after the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Some emerging studies have shown that social movements facilitate immersive travel or establish “movement schools” (Isaac, Jacobs, Kucinskas, & McGrath, 2020) for the express purpose of instilling participants with prosocial attitudes. For example, Adler (2019) and Russo (2014) have both published studies of U.S. immigrant rights organizations that facilitate travel immersion programs, bringing U.S. citizens face‐to‐face with the harsh realities of life on the U.S.‐Mexico border. Their studies show that people who participate in activities such as walking across hot deserts report higher levels of prosocial attitudes, specifically compassion and empathy toward immigrants.…”
Section: Prosocial Outcomes Of Social Movementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some emerging studies have shown that social movements facilitate immersive travel or establish “movement schools” (Isaac, Jacobs, Kucinskas, & McGrath, 2020) for the express purpose of instilling participants with prosocial attitudes. For example, Adler (2019) and Russo (2014) have both published studies of U.S. immigrant rights organizations that facilitate travel immersion programs, bringing U.S. citizens face‐to‐face with the harsh realities of life on the U.S.‐Mexico border. Their studies show that people who participate in activities such as walking across hot deserts report higher levels of prosocial attitudes, specifically compassion and empathy toward immigrants.…”
Section: Prosocial Outcomes Of Social Movementsmentioning
confidence: 99%
“…Their studies show that people who participate in activities such as walking across hot deserts report higher levels of prosocial attitudes, specifically compassion and empathy toward immigrants. Additionally, Russo (2014) produces evidence that participants who report higher levels of empathy toward immigrants in turn engage in prosocial activities upon returning home; she writes of one participant who began volunteering at a local migrant rights organization, where she was “involved in community education, abuse documentation, etc.” (p. 74), and another participant who left an administrative position in a hospital to become “a Spanish teacher for students with disabilities” (p. 74). However, Adler (2019) cautions that increased empathy does not always translate into action, as most of the participants surveyed did not engage in any volunteer work with immigrant populations upon returning home (p. 214).…”
Section: Prosocial Outcomes Of Social Movementsmentioning
confidence: 99%
“…Social movement scholars have often minimized the importance of ally organizations, believing them to be ineffective and short-lived due to allies' often minimal personal stake in the issues being addressed (Marx and Useem 1971;Myers 2008). In recent years, however, some scholars have given ally organizations greater attention by pointing to examples of their efficacy, such as "straight" ally organizations working to advance LGBT interests (Myers 2008; for other examples see Dixon et al 2013;Russo 2014). Furthermore, campaigns like Black Lives Matter are reviving questions about whether and how allies should be involved in such movements Roediger 2016).…”
Section: Representative Group Styles: How Ally Immigrant Rights Organmentioning
confidence: 99%
“…Furthermore, campaigns like Black Lives Matter are reviving questions about whether and how allies should be involved in such movements Roediger 2016). Some scholars underscore the importance of understanding ally organizations because of their prevalence, potential for coalition-building, and occasional efficacy (Dixon et al 2013;Myers 2008;Russo 2014). Others highlight how organizations that span social divides, such as ally organizations, can increase marginalized groups' access to elites and help generate the cultural and social capital needed to challenge existing systems of power (Bystydzienski and Schacht 2001;Rose 2000).…”
Section: Representative Group Styles: How Ally Immigrant Rights Organmentioning
confidence: 99%
“…The existing work on allies presumes that they are an asset to movements, and for that reason they have remained of sociological interest. McCarthy and Zald (1977) theorized that allies were important for resource mobilization of social movements, and recent work has echoed the significant role of allies throughout U.S. history (Russo 2014). Movement scholars have also recognized the importance of allies in identity-based movements such as whites in the Black Civil Rights movement (e.g., Brown 2002) and men in feminist movements (e.g., Messner, Greenberg, and Peretz 2015).…”
mentioning
confidence: 99%